Post-impoundment population dynamics of non-native common carp Cyprinus Carpio in relation to two large native cyprinids in Lake Gariep, South Africa - Winker, Henning (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2011)
To contribute to the understanding of the invasion biology of common carp Cyprinus carpio in southern Africa, this thesis investigated the life history, relative abundance, long-term population demographics and trophic niche utilisations of non-native common carp C. carpio in relation to two endemic cyprinids, Orange River mudfish Labeo capensis and smallmouth yellowfish Labeobarbus aeneus in South Africa"Ÿs largest impoundment, Lake Gariep. The growth zone deposition rates in astericus otoliths of the three species were validated as biannual for C. carpio and as annual for L. capensis and L. aeneus, which allowed for reliable estimation of lengths-at-age upon which growth, age-at-maturity and mortality rates could be estimated. Cyprinus carpio exhibited fast growth, matured relatively early at two years of age and attained a maximum age of seven years. Labeo capensis grew significantly slower, but attained older ages of up to 12 years. Females showed notably delayed maturation at approximately six years of age. The life history parameter estimates for L. aeneus were similar to those of L. capensis. These species-specific life history characteristics contributed to a substantially higher population growth potential of C. carpio compared to L. capensis and L. aeneus. Delta-lognormal and delta-gamma Generalized Linear Models (GLMs) were used to analyse patterns of relative abundance of L. capensis, L. aeneus and C. carpio. The application of these GLMs was necessary to account for large proportions of zeros and strong skewness in the catch-per-unit-effort (CPUE) from experimental gillnet and fisheries-dependent angler surveys. Confidence intervals around predicted abundance indices were obtained through the development of a generalised parametric bootstrap procedure. The resulting standardised abundance indices were coupled with results from analysis of stable isotope ratios of fish tissues and potential food resources and revealed that C. carpio was mainly confined to soft-bottom habitats, where it predominantly foraged on benthic invertebrates. Labeo capensis was abundant in a wide range of benthic habitats and was consumed basal food resources such as detritus. Labeobarbus aeneus was found to feed mostly on pelagic zooplankton. There were no significant interspecific differences in trophic niche space, suggesting limited resource competition among the three species. Standardised historical and contemporary gillnet CPUE data indicated slow population growth rates of L. capensis and L. aeneus during the first ten years postimpoundment, but showed high biomass levels some four decades after impoundment. These results could be corroborated by stochastic age-structured production model (ASPM) simulations. In contrast to the two endemic species, the gillnet CPUE of C. carpio showed a clear boom and bust"Ÿ pattern, which, based on ASPM simulations, could be best explained by increased food availability during the first five years postimpoundment, followed by suboptimal conditions thereafter. Together, these results provided evidence that the establishment of the C. carpio population did not prevent the slow but successful long-term establishment of the two large endemic cyprinids. Both endemic fishes revealed specialised feeding within the impoundment.
Keywords: Cyprinidae -- South Africa -- Gariep Dam; Carp -- South Africa -- Gariep Dam; Fish populations -- South Africa -- Gariep; Dam Fishes -- Physiology -- South Africa -- Gariep Dam; Barbus aeneus -- South Africa -- Gariep Dam; Mudfishes -- South Africa -- Gariep Dam; Freshwater fishes -- South Africa -- Gariep Dam